2006
DOI: 10.1002/bio.914
|View full text |Cite
|
Sign up to set email alerts
|

An assay for inorganic mercury(II) based on its post‐catalytic enhancement effect on the potassium permanganate–luminol system

Abstract: A strong chemiluminescence (CL) response is observed when potassium permanganate solution is injected into basic luminol solution. When the CL reaction terminates, subsequent injection of Hg2+ solution into the reaction mixture results in a new CL reaction. Based on the post-catalytic enhancement effect of Hg2+ on the potassium permanganate-luminol system in basic media, a fast and simple CL-coupled flow injection analysis for the determination of Hg2+ was developed. In optimum conditions, CL intensity is prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In an optical microplate assay, product formation can be measured directly without any prior analyte preconcentration step or a later purification step for product. It is reported that among the optical techniques, chemiluminescence can be used for heavy metal analysis as the instrumental setup is relatively simple, free from instrumental interferences and highly sensitive [ 26 28 ]. There is significant interest toward miniaturization of analytical systems, since it allows the handling of low volume samples, reduction in waste generation and reagent consumption with increased sample throughput [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an optical microplate assay, product formation can be measured directly without any prior analyte preconcentration step or a later purification step for product. It is reported that among the optical techniques, chemiluminescence can be used for heavy metal analysis as the instrumental setup is relatively simple, free from instrumental interferences and highly sensitive [ 26 28 ]. There is significant interest toward miniaturization of analytical systems, since it allows the handling of low volume samples, reduction in waste generation and reagent consumption with increased sample throughput [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…[21] In addition, Hu et al reported a CL method for the determination of inorganic mercury (II) based on its post-catalytic enhancement eff ect on the potassium permanganate-luminol system. [22] Recently, there have been four reported procedures in the literatures for the determination of berberine in tablet or capsules using fl ow injection with CL detection. These procedures are based on the inhibition of berberine hydrochloride in the CL reaction of luminol-vanadomolybdophosphoric heteropolyacid-sodium hydroxide system, [23] the enhancement action of berberine hydrochloride on the weak CL of a cobalt (II)-hydrogen peroxide-hydrogencarbonate system [24] or cerium (IV)-Ru (bipy) 3 2+ system, [25] and the CL reaction of a potassium permanganate-berberine hydrochloride-polyphosphoric acid system.…”
Section: Introductionmentioning
confidence: 99%